A Pitești-i Református Egyházközség első tíz évének demográfiai adatsorai a halálozási anyakönyvek tükrében - PÉTER, István (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
Demographic Data of the First Ten Years of Existence of the Pitești Reformed Church in the Light of the Official Death Registries. In the last three centuries, many Hungarians in Transylvania went to work and live in the southern part of the Carpathians. At first, they went just for se-asonal work, but later they become permanent migrants. They founded new Re-formed parishes and schools in the new locations. We have data on the population of Pitești from 1844, when Sándor Ürmösy described the ethnic and confessional composition of the town for the first time, and he mentions 1,500 Hungarians in Pitești. As result of the Reformed missio-nary work, the first Reformed churches were established in the most important towns of old Romania in the mid-19th century. The documents of those times reveal to us data on the demographic, confessional, and ethnic composition of the population. In this study, I attempted to find the most important data on the first ten years in the life of the Pitești Reformed community linked to its members’ age of death, cause of the death, and occupation.